Imigração de mulheres haitianas: um olhar para o caso de reunificação familiar - Buaski, Sandra (2021)
Immigration is a process that is part of history and life. The immigration of many Haitians intensified, especially to Brazil, from 2010, and to the city of Pato Branco, in 2012. First, there was an arrival of a mostly male group, aiming to find work in local agro-industries. With this group, Haitian women come to the city with the aim of bringing families together. Based on this context, this research sought to analyze, from the perspective of Haitian women living in the city of Pato Branco-PR, difficulties and challenges faced by them for family reunification. For that, an exploratory research was carried out, whose data collection took place through semi-structured interviews applied to 10 participants. Data analysis was qualitative based on the following categories of analysis: immigration; immigration of Haitian women; family meeting; sons; difficulties and challenges to reunite the family. The results show that Brazilian laws guarantee family reunification and when the immigrant meets the criteria imposed by the legislation, immigration becomes safer. Haitian women look to immigration as a way out of the difficulties experienced in their country, Haiti. With that, the interviewees headed to Brazil to live with their family and find better opportunities. The main challenges for family reunification, in the eyes of immigrant women, are diverse. Among them is the difficulty in getting a job, both for those who arrive first and need to find stability to then request the arrival of other family members, as for those who arrived later and need to place themselves in the labor market, to help with expenses and send remittances financial support for those who remained in their country of origin; the lack of command of the Portuguese language, because, due to this limitation, immigrants take longer to find work; the difficulty in finding housing is also a challenge reported by immigrants, as they need guarantors and it is common for large numbers of immigrants to reside in the same house. These factors directly interfere and hinder the process of family reunification of immigrants.